Evaluation and Diagnostic Potential of Serum Ghrelin in Feline Hypersomatotropism and Diabetes Mellitus. (January 2015) - Jensen, K.B.; Forcada, Y.; Church, D.B.; Niessen, S.J.M.
<x xml:space="preserve">Abstract</x> Background Ghrelin is a growth hormone secretagogue. It is a potent regulator of energy homeostasis. Ghrelin concentration is down‐regulated in humans with hypersomatotropism (HS) and increases after successful treatment. Additionally, ghrelin secretion seems impaired in human diabetes mellitus (DM). Hypothesis Serum ghrelin concentration is down‐regulated in cats with HS‐induced DM (HSDM) compared to healthy control cats or cats with DM unrelated to HS and increases after radiotherapy. Animals Cats with DM (n = 20) and with HSDM (n = 32), 13 of which underwent radiotherapy (RT‐group); age‐matched controls (n = 20). Methods Retrospective cross‐sectional study. Analytical performance of a serum total ghrelin ELISA was assessed and validated for use in cats. Differences in serum ghrelin, fructosamine, IGF‐1 and insulin were evaluated. Results Ghrelin was significantly higher (P < .001) in control cats (mean ± SD: 12.9 ± 6.8 ng/mL) compared to HSDM‐ (7.9 ± 3.3 ng/mL) and DM‐cats (6.7 ± 2.3 ng/mL), although not different between the HSDM‐ and DM‐cats. After RT ghrelin increased significantly (P = .003) in HSDM‐cats undergoing RT (from 6.6 ± 1.9 ng/mL to 9.0 ± 2.2 ng/mL) and the after RT ghrelin concentrations of HSDM cats were no longer significantly different from the serum ghrelin concentration of control cats. Serum IGF‐1 did not significantly change in HSDM‐cats after RT, despite significant decreases in fructosamine and insulin dose. Conclusion and Clinical Importance Ghrelin appears suppressed in cats with DM and HSDM, although increases after RT in HSDM, suggesting possible presence of a direct or indirect negative feedback system between growth hormone and ghrelin. Serum ghrelin might therefore represent a marker of treatment effect.